THE USE OF FLOWCHART AS A METHOD OF SALES PROCESS ANALYSIS: A STUDY OF THE WEAKNESSES, RISKS AND EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS - Adinda Naya Salsabilla; Ardhina Dwi Sabtara; Divyana Aprila Daung Salsabilla (Universitas Sam Ratulangi, 2026)
This study aims to analyze the sales process using flowcharts as a tool for mapping workflows in Accounting Information Systems. Flowcharts are used to identify procedural stages, decision points, and parties involved in the sales process. This study uses a literature review method to examine the types of risks that arise, including fraud, delays in authorization, and inaccurate documentation, as well as to assess the effectiveness of the Accounting Information System in supporting sales activities. The results show that flowcharts provide a clear visualization of operational flows, facilitating the evaluation of inefficiencies, risk gaps, and inaccuracies in internal controls. In addition, the use of flowcharts has been proven to help improve understanding of data integrity and document flow, thereby contributing to the improvement of the overall effectiveness of the accounting information system. This study confirms that flowcharts are an effective tool for business process analysis and development, particularly in the sales cycle. Keywords: Flowchart, Sales Process, Risk Assessment, Accounting Information System Effectiveness.